IMPLEMENTATION OF TRANSPORT SECTOR DECARBONIZATION POLICY IN THE MAMMINASATA URBAN AREA - Said, Sabery; Anshar, Muh.Ashary; Sujatmiko, Sujatmiko (Yayasan Education and Social Center, 2025)
The transport sector contributes significantly to greenhouse gas (GHG) emissions in the Mamminasata metropolitan region. This study examines the implementation of transport sector decarbonization policy through strategic and operational perspectives by evaluating institutional roles, inter-agency coordination, and stakeholder engagement. The main objective is to develop a contextual roadmap that supports a transition to low-emission transportation. The study employs a qualitative approach with an exploratory case study design. Data were collected through in-depth interviews with local government agencies, transport operators, and community organizations, as well as analysis of policy documents (RPJMD, SUMP, NDC, and IGRK). The data were analyzed thematically and triangulated using perspectives from strategic management (Fred R. David), total quality management (W. Edwards Deming), and the theory of constraints (Eliyahu Goldratt). The findings reveal the existence of normative frameworks, but their implementation lacks alignment. Institutional fragmentation, weak regulatory integration, and low community adoption of low-emission transport modes further hinder progress. These results highlight the need for institutional consolidation, measurable performance indicators, and a legally supported policy roadmap to operationalize a sustainable urban transport system. This research contributes to strategic transport management literature by providing an empirical basis for actor-based coordination and context-driven transformation. It also recommends developing performance indicators and policy measures to accelerate decarbonization in urban mobility systems. Keywords: Strategic management; operational management; transport decarbonization; institutions; policy roadmap; Mamminasata.